“I Played Video Games and I Picked Up the Language”: Exploring L2 Acquisition Through Extensive Listening/Viewing - Ardianto, Puthut; Erdita Dwi Pramesti; Lanoke Intan Paradita; Purwanto, M Bambang (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The development of 21st-century learning is marked by the use of information and communication technology. Video games are one of the media that can be used by students in learning languages, especially English. Learning using video games can motivate students more and help students adapt to the lesson. This study aims to determine what types of games are used by students to learn English and to determine students' perceptions about playing video games for learning English. In this study, the researcher formulated two questions. This study uses a descriptive qualitative research design and the data collection technique that the researcher uses is interviews. The participants in this study were eight students of English language education department class at private university in Yogyakarta. Based on the data obtained by the researcher, there are several games played by students to learn English such as Mobile legend, League of Legends, PUBG, Pro Evolution Soccer, God of War, Dota2, Call of Duty, Mortal Kombat Shaolin Monk, Zelda, and Hidden Object. In addition, video games can also provide some benefits in learning English. The benefits obtained are make learning fun, increase motivation, facilitate students to learn new English vocabulary, facilitate students to practice their language skills such as reading, listening and speaking skills.